Celebrating two decades of SBSI (2004 to 2023): A Comprehensive Descriptive and Meta-Scientific Analysis - Carvalho, Luiz Paulo; Lima, Silas; Brandão, Michele A.; Marinho, Élton Carneiro; Silva, Mônica Ferreira Da; Oliveira, Jonice; Santoro, Flavia Maria (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: SBSI ties together the Brazilian Information Systems community since 2004, 20 years ago. Through their research, the community has matured, grown and established, through authorships, institutions, research interests, and collaborations. Problem: complexity, diversity and plurality grew as the SBSI, and IS community, grew and spread; presenting self-monitoring challenges. There are few meta-scientific studies covering collaborations and quantitative studies, in different dimensions. Solution: we conducted a comprehensive and complete study, analyzing several SBSI aspects, with a materialistic emphasis on authorship (3595) and studies (1052), covering all 19 years of the event. IS Theory: Argumentative theory, Critical social theory. Method: we conducted a descriptive-analytical study, similar to a scope review. We use quantitative analyzes and Social Network Analysis techniques, prioritizing a temporal perspective, exposing the evolution of phenomena. We deal with different dimensions and interrelate the appropriate or plausible ones. Summarization of Results: this work reiterates or enriches the findings of previous works. Reinforces a low number of female authors, while several of the most prolific authors are women. As institutions, USP, UNIRIO, UFPE, UFRJ and UNISINOS stand out. The Southeast region, Rio Grande do Sul and Pernambuco stands out. Collaborations and authorship numbers differs. Brazilian Portuguese predominates as the main language, except in 2021, an outlier. The keywords are reflect an emphasis on information systems. Contributions and Impacts on the IS area: we present a multidimensional Brazilian IS panorama understanding, for better meta-scientific and organizational decision-making. It serves as input and complement to think about Brazilian IS challenges, current and future.